ANALISIS PEMBENTUKAN KARAKTER TANGGUNG JAWAB SEKOLAH BERASRAMA SISWA KELAS IV MADRASAH IBTIDAIYAH MA'HAD AL-ZAYTUN - Supriyati, Wiwin; Mardani, Dadan; Iswandi, Irvan (Sindoro: Cendikia Pendidikan, 2024)
This research analyses the character building of responsibility in boarding school for grade IV students of Madrasah Ibtidaiyah Ma'had Al-Zaytun. The purpose of this research is to find out how the boarding school life activities of grade IV students of Madrasah Ibtidaiyah Ma'had Al-Zaytun as well as how Ma'had Al-Zaytun Educational Institution in shaping the responsibility character of grade IV students of Madrasah Ibtidaiyah Ma'had Al-Zaytun through boarding school life activities. The research method used by the researcher is to use a qualitative research approach, with the type of research chosen, namely case studies and field research. With data search procedures through interview techniques, observation and documentation. The sampling technique with purposive sampling technique. Observations made by researchers are with passive participation techniques. For data analysis using the concept of Miles and Huberman. And to check the validity of the data through the source triangulation test. The results of this study show that boarding school life activities for fourth grade students of Madrasah Ibtidaiyah Ma'had Al-Zaytun refer to the unsyitoh yaumiyah (daily activities) of students from waking up to sleeping again which is routinely carried out from 04.30 to 19.30, coupled with development activities from the unsyitoh yaumiyah programme. As for the formation of responsibility character in grade IV students of Madrasah Ibtidaiyah Ma'had Al-Zaytun, which includes the formation of responsibility character as follows: 1) Character building of responsibility towards God Almighty 2) Character building of responsibility towards oneself 3) Character building of responsibility for the social environment / society 4) Formation of character responsibility towards others 5) Formation of character responsibility towards the state Keywords: Responsibility Character, Boarding School